Cholecysto-appendicostomy as partial internal biliary drainage in Progressive Familial Intrahepatic Cholestasis Type 1: A case report and review of literature - Yik, Y.I.; Othman, M.Y.; Ng, R.T.; Lee, W.S. (Elsevier, 2016)
Intractable pruritus secondary to bile salts retention in Progressive Familial Intrahepatic Cholestasis (PFIC) can be relieved surgically by diverting bile drainage from ileum to reduce bile salts reabsorption into entero-hepatic circulation. We are reporting on the successful biliary diversion in a child with PFIC, with the use of the appendix as a conduit to drain bile from gallbladder to the colon (cholecysto-appendicostomy).